Is Caesarean Myomectomy a Safe Procedure? A Comparative Study - Başaranoğlu, Serdar; Ağaçayak, Elif; Deregözü, Ayşegül; Gümüş, İlknur İnegöl; Acet, Mustafa; Gül, Talip (Gynecology Obstetrics & Reproductive Medicine, 2016)
OBJECTIVE: Uterine myomas are the most common benign pelvic tumours observed during the reproductive period.Increased risks of haemorrhage and postoperative morbidity lead professionals to avoid myomectomy at the time of Cesarean (C-section). The present study retrospectively analysed the data of patients who had undergone C-section only and those that had undergone C-section and simultaneous myomectomy. STUDY DESIGN: The data of 42 patients (Group 1) who had underwent caesarean myomectomy and of 50 patients underwent C-section only (Group 2) out of 92 patients that had been taken into C-section on the basis of obstetric indications were retrospectively analysed in this study. The relevant patient data were recorded with the inclusion of demographic data, gestational week, and preoperative and postoperative laboratory findings. Types, locations and sizes (the largest diameter) of individual myomas were identified and noted. RESULTS: The mean diameter of myomas was 66.3±30.2 mm. Ten patients that had underwent caesarean myomectomy (23.8%) developed a need for intensive care. No statistically significant difference was found in laboratory parameters between Group 1 and Group 2. CONCLUSION: Caesarean myomectomy, when performed by experienced obstetricians, does not lead to a significant increase in maternal morbidity and mortality. Although the short-term effects of this procedure are known, there is a need for the conduct of more comprehensive studies to establish its longterm effects on fertility or how it will affect the next pregnancy processes.